MODEL INKUIRI LEARNING UNTUK MENINGKATKAN HASIL BELAJAR DAN KEMAMPUAN BERPIKIR KRITIS SISWA - Dolewikou, Rina; Watloly, Aholiab; Septory, Jekriel (Jurnal Manajemen Pendidikan, 2025)
One of the subjects that has an important role in character building is Pancasila Education. This subject aims to instill the nation's noble values ​​​​such as social justice, mutual cooperation, tolerance, and love of the homeland which are expected to be internalized in students' attitudes and behavior. This study aims to improve the learning outcomes of Pancasila Education in fifth grade students of Tounwawan Christian Elementary School through the application of the inquiry learning model. The background of the study is the low understanding of students regarding rights and obligations, as seen from the results of the initial test which showed that only 30% of students achieved the Minimum Completion Criteria (KKM) with an average of 55.5. This study used the Classroom Action Research (CAR) method of the Kemmis & McTaggart model in two cycles with 10 students as subjects. Data were collected through learning outcome tests, observations, and reflections, then analyzed descriptively. The results showed an increase in the average student score from 55.5 (30% completion) in the initial condition, to 68.5 (50%) in cycle I, to 82.8 (100%) in cycle II. In addition to quantitative improvements, students become more active in asking questions, discussing, and presenting learning outcomes. Thus, inquiry learning has been proven effective in improving learning outcomes while fostering critical thinking skills, self-confidence, and collaboration.